Range of Motion (ROM) Induced by Shape Memory Alloy (SMA) Actuation on Stewart Platform for Foot/Ankle Rehabilitation - SUBRAMANIAM, KRISHNAN (2017)
Foot/Ankle injuries are considered to be the single leading cause of adult disability worldwide. In Malaysia, there are approximately 10,000 new foot/ankle stroke cases each year and new rehabilitation devices are needed to perform the rehabilitation foot/ankle. The limitation of existing rehabilitation devices such as range of motion (ROM) and sudden actuation with air pressure or electric motor mislead the patient’s injuries. Currently, Stewart platform rehabilitation devices are actuated by various methods including double acting pneumatic cylinder, hydraulic and electric motor. The limitation of using these actuation methods is that the platform cannot promote the continuous passive motion required for foot/ankle rehabilitation because of the fast and sudden movement of the platform that can cause further foot/ankle injury. The objectives of this study are to develop Stewart platform test-rig, to analyze novel Stewart platform using shape memory alloy (SMA) wires, to generate the Stewart platform model for angle and force using response surface methodology techniques and to evaluate the performance of the Stewart platform. In this research study Stewart platform with upper platform diameter 150 mm and 300 mm actuated by various diameters of shape memory alloy (SMA) wires using electric current and temperature is presented. The 150 mm Stewart platform actuated by Ø 0.508 mm SMA wire produced maximum platform angle of 24.8° with a force of 9.6 N whereas, the 300 mm Stewart platform actuated by Ø 0.508 mm SMA wire produced maximum platform angle of 24.78° with a force of 9.6 N. The developed Stewart platform produced 24.8° range of motion (ROM) as comparing to the other researches findings with a limited of ROM up to 20°. Performance of the prototype through experimental and theoretical results has proven relevant. This shows an improvement of the current work with the previous work.